Horizontes transversais: artes da imagem e do som em Minas Gerais (2000-2010). - Ana Moraes Vieira (2012)
A brief critical overview of artistic production audiovisual held in Minas Gerais in the first decade of this century, from artists who articulated concepts, thematic and formal studies with other fields of visual arts. Discusses the recent history of video in Brazil and, more specifically, in Minas Gerais, where the actual video dimensions expand and assert themselves beyond the support. We chose to construct the trajectory of the formal use of video as artistic support through specific references to understand the historical background and meet with the most recent settings through interviews with artists and researchers.